Regaining the dream how to renew the promise of homeownership for America's working families - Quercia, Roberto G. 1953- (Brookings Institution Press, 2011)
"Backed by extensive study of mortgage loans made to low-income Americans over a ten-year period, argues that in the wake of the financial crisis of 2008-09, lenders need not shy away from the low-income as risks but institute equitable and sustainable homeownership policies that include correctly structured loans"--Provided by publisher.